PENGELOLAAN MASJID PARIPURNA AL-MUTTAQIN KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2018 - Rocky Andreas; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Paripurna Mosque is a mosque that has good management, adequate facilities and a center for community religious activities that can be used as an example in the management of mosque management in Pekanbaru City. In Regional Regulation No. 2 of 2016 concerning Pekanbaru City Paripurna Mosque, it is explained that there are three important aspects in the management of plenary mosque, namely Idarah, Imarah and Ri'ayah. That in the aspect of imarah the reality is that the Al-Muttaqin Paripurna Mosque in the tampan District of the mosque management tends to be far from the prosperity of the mosque. It is suspected that the mosque's financial problems have not been well managed and accompanied by people who prosper it. The purpose of this study is to describe the management of activities in the field of the Imarah of the Al-Muttaqin Paripurna Mosque, Tampan District, Pekanbaru City as seen from the management functions of planning, organizing, implementing, budgeting, and monitoring activities. This study uses a qualitative research with a descriptive approach conducted at the Al-Muttaqin Paripurna Mosque, Tampan District, Pekanbaru City. The results of this study can be seen that the function of planning the activities of the direction of the priesthood can be said to be maximal and is already quite active. However, there are still two programs that have not been maximized, namely the education sector and mosque youth. In the function of organizing the activities of the Emirate it has been arranged in accordance with the instructions of Regional Regulation No. 2 of 2016 concerning the Paripurna Mosque of Pekanbaru City. The fact is that in the field the manager is not lacking in personnel but many of the administrators and worshipers who when there are Imarah activities at the Al-Muttaqin plenary mosque did not participate. In the function of the implementation of the activities of the pilgrimage it can be said to have been implemented well, although at times it is not carried out, this is caused by the lack of budget to carry out many programs of the activities of the pilgrimage. In the budgeting function of the immigration activity the source of funds for the implementation of the immigration activities in the budget mosque comes from the infa pilgrims. In the function of supervising Imarah activities is very rarely done, since the Al-Muttaqin mosque was designated a plenary mosque, supervision of the evaluation team was only done once in 2017. Keywords: Planning, Organizing, Actuating, Budgeting, Controling.